2006
DOI: 10.1074/jbc.m511075200
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Sensing in Saccharomyces cerevisiae Is Mediated by a Conserved DNA Element and Requires the Activity of Biotin-Protein Ligase

Abstract: Biotin is a water-soluble vitamin that functions as a prosthetic group in carboxylation reactions. In addition to its role as a cofactor, biotin has multiple roles in gene regulation. We analyzed biotin effects on gene expression in the yeast Saccharomyces cerevisiae and demonstrated by microarray, Northern, and Western analyses that all yeast genes encoding proteins involved in biotin metabolism are up-regulated following biotin depletion. Many of these genes contain a palindromic promoter element that is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…The same promoter fragment was fused to a full-length lacZ gene in a centromeric vector to give the reporter plasmid used in Fig. 5B (46). The yeast genomic library in the CEN-TRP1 vector pRS200 was described before (16) and obtained from the American Type Culture Collection (ATCC 77164).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same promoter fragment was fused to a full-length lacZ gene in a centromeric vector to give the reporter plasmid used in Fig. 5B (46). The yeast genomic library in the CEN-TRP1 vector pRS200 was described before (16) and obtained from the American Type Culture Collection (ATCC 77164).…”
Section: Methodsmentioning
confidence: 99%
“…Growth assays on agar plates were performed according to published methods (55). Biotinylated proteins were detected in whole-cell extracts using streptavidin-coupled peroxidase (strep-PO) as described previously (46). To remove strep-PO from desthiobiotinylated proteins, Western blots were incubated for 16 h in TBST (Tris-buffered saline with 0.05% Tween 20) buffer containing 2 mM desthiobiotin and 1% bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Pirner and Stolz reported that, in yeast, the concentration of biotin in the culture medium affects the expression of the genes involved in biotin synthesis and transport. 31) The promoter region in these genes has a common nucleotide sequence, namely, the biotin response element (BRE), and a tentative transcription factor(s) is thought to bind to BRE in response to the intracellular biotin level to reduce the expression of these genes. We discovered in this experiment that the mRNA levels of at least 6 genes (PCK1, G6PC, HNF4, PGC-1, biotinidase, and PCCA) were significantly decreased by the biotin administration.…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid was constructed in two steps. First, the MEL1 minimal promoter containing a fragment of the VHT1 pro-moter (Pirner and Stolz 2006) was ligated into the PstI and BamHI sites of YEplac195-GFP. Next, the VHT1 fragment was replaced with a PCR product containing the Put3 binding site (À501 to À486 bp relative to the start ATG of MCH5) along with 24 bp of upstream and 23 bp of downstream sequence.…”
Section: Yeast Strainsmentioning
confidence: 99%